Speech acts in Madagascar 3 (A film) and their application in ELT - Rahmawati, Herlin (LingTera, 2017)
This research aims to: (1) identify and describe speech acts in the film of Madagascar 3: Europe’s Most Wanted that suit to the language functions in KTSP and 2013 Curriculum for junior high school and (2) explain ways to apply the speech acts in ELT. This study employed the qualitative approach. The research object consisted of the utterances in the film. The data were collected through an observation and they were classified based on the speech act classification. The research findings reveal that there are many speech acts functions in the film suiting to the language functions in the curriculums. Directive speech act includes commanding and ordering, requesting, inviting, suggesting, prohibiting, and begging. Expressive speech act includes parting, thanking, congratulating, liking and disliking, greeting, apologizing, complimenting and admiring, agreeing and disagreeing, doubting, and refusing. Representative speech act includes convincing, informing, and giving fact or opinion. Commissive speech act includes promising and offering. The application of the speech acts functions in ELT is done by making use of the utterances to express the language functions in the curriculums.